Outdoor performance of GaAs/bifacial Si heterojunction four-terminal system using optical spectrum splitting. (15th July 2022) - Scuto, A.; Corso, R.; Leonardi, M.; Milazzo, R.G.; M. S. Privitera, S.; Colletti, C.; Foti, M.; Bizzarri, F.; Gerardi, C.; Lombardo, S.A.
Graphical abstract: Highlights: Analyzed the outdoor performance of a realized bifacial four-terminal device. Observed a constant 17% efficiency increase due to bifaciality impact. Achieved a maximum efficiency value of 25.4% in outdoor conditions. Measured a significant shift of solar spectrum during the day towards IR region. Showed the robustness of the bifacial 4T device to spectrum daily variations. Abstract: Bifacial photovoltaics and multijunction systems represent the most promising alternatives to overcome the theoretical limit of single-junction Si photovoltaics, and these solutions can also be combined to achieve higher performances. This work investigates the outdoor performance of a bifacial four-terminal photovoltaic system based on combining a III-V semiconductor with the silicon heterojunction technology. By exploiting the wide band gap energy of GaAs, the bifaciality of the Si heterojunction and the spectrum-splitting capability of dichroic mirrors, an optimal voltage match between mini-modules of the two solar cells was achieved, with an open-circuit voltage mismatch of 4% of the average value. In this study, we demonstrate the full functionality of bifacial operation with a 17% increase of power conversion efficiency throughout the day compared to monofacial operation. Furthermore, we show that though the solar spectrum is subjected to strong variations from morning to afternoon, which lead to changes of the ratio of the GaAs to the Si mini-module short-circuit currents up to 43% throughout the day, the variation of the overall system power conversion efficiency remains quite limited, less than 16% of the maximum value thanks to the efficient coupling of the two mini-modules.